Entrepreneurial Vernacular Developers' Subdivisions in the 1920s - Loeb, Carolyn S., 1948-; Project Muse.; Project Muse. (2019)
Suburban subdivisions of individual family homes are so familiar a part of the American landscape that it is hard to imagine a time when they were not common in the U. S. The shift to large-scale speculative subdivisions is usually attributed to the period after World War II. In Entrepreneurial Vernacular: Developers' Subdivisions in the 1920s, Carolyn S. Loeb shows that the precedents for this change in single-family home design were the result of concerted efforts by entrepreneurial realtors and other housing professionals during the 1920s. In her discussion of the historical and structural forces that propelled this change, Loeb focuses on three typical speculative subdivisions of the 1920s and on the realtors, architects, and building-craftsmen who designed and constructed them. These examples highlight the "shared set of planning and design concerns" that animated realtors (whom Loeb sees as having played the "key role" in this process) and the network of housing experts with whom they associated. Decentralized and loosely coordinated, this network promoted home ownership through flexible strategies of design, planning, financing, and construction which the author describes as a new and "entrepreneurial" vernacular.
Introduction : The entrepreneurial vernacular subdivision : Entrepreneurial vernacular ; The emergence of a housing solution in the 1920s ; The subdivisions and their builders ; Agency, form, and meaning -- Part I. Three subdivisions and their builders : 1. The Ford Homes: the case of the borrowed builders : The Ford Homes: background and overview ; The Ford Homes: design and construction ; The development of industrialized building ; relations of production ; Modeling efficient development -- 2. Brightmoor: the case of the absent architect : Brightmoor: background and overview ; B.E. Taylor and the development of Brightmoor ; The absent architect ; Situating Brightmoor -- 3. Westwood Highlands: the rise of the realtor : Westwood Highlands: background and overview ; The role of style ; The principles of organization ; Realtors: the professional project ; Realtors as community builders ; Rationalizing development -- Part II. Agency, form, and meaning : 4. The home-ownership network: constructing community : The prevalence of the single-family detached suburban house ; The home-ownership network ; The neighborhood unit plan ; Communities on the ground -- 5. Architectural style: The charm of continuity : The Ford Homes ; Brightmoor ; Westwood Highlands ; Stylistic pluralism ; The charm of continuity -- Conclusion: Architecture as social process : Distilling a new vernacular ; Entrepreneurial vernacular and the landscape exchange.
The text of this book is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License
Open access edition supported by the National Endowment for the Humanities / Andrew W. Mellon Foundation Humanities Open Book Program.
Includes bibliographical references (pages 215-258) and index.
Description based on print version record.
Keywords: Real estate development; Land subdivision; Housing; Real estate development -- United States -- History; Housing -- United States -- History; Land subdivision -- United States -- History; United States; Electronic books; History; Electronic books